Preparation of nanocrystalline Pd/SnO2 thin films deposited on alumina substrate by reactive magnetron sputtering for efficient CO gas sensing. (April 2022) - Gangwar, Amit Kumar; Godiwal, Rahul; Srivastava, Stuti; Pal, Prabir; Gupta, Govind; Singh, Preetam
Highlights: Single step process of SnO2, Pd/SnO2 thin films deposition by reactive magnetron sputtering for efficient CO sensing. A maximum sensor response > 90% for 91 ppm CO gas at 200 °C operating temperature for Pd/SnO2 is realized. An excellent sensor response > 65% at a relatively low operating temperature of 100 °C for Pd/SnO2 is achieved. Prepared Pd/SnO2 thin films are found to be highly selective towards CO gas. Abstract: We have prepared nanocrystalline Pd/SnO2 thin films deposited on alumina substrate by reactive magnetron sputtering for highly sensitive and selective CO gas sensing. The deposited thin films have a nanocrystalline nature and uniform granular morphologies as characterized by GIXRD and FESEM, respectively. The oxidation states and defect states were measured using XPS and PL spectra, respectively. The sensing performance of samples for CO gas was recorded at different conditions. An enhanced sensing performance of Pd/SnO2 (sensor response, SR ∼ 90.5% with fast response/recovery time ∼ 15 s/34 s) was achieved compared to pristine-SnO2 film (SR ∼ 81.7% and response/recovery time ∼ 60 s/98 s) for 91 ppm CO gas at 200 °C operating temperature. Further, Pd/SnO2 film exhibits an excellent SR ∼ 65.5% even at 100 °C operating temperature. Thus, the prepared nanocrystalline Pd/SnO2 thin films can be used for the fabrication of CO gas sensors with efficient sensing performance. Graphical abstract: Image, graphical abstract